2021
DOI: 10.1080/07421656.2021.1922328
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Depression—A 6-Month Follow-up of a Randomized Controlled Study of Manual-Based Phenomenological Art Therapy for Persons With Depression

Abstract: Manual-based phenomenological art therapy (PATd) was developed to facilitate recovery from depression. The study's aim was to investigate whether improvements were maintained 6 months after PATd was completed. In a randomized controlled study design, persons diagnosed with moderate or severe depression (n ¼ 85) were invited to take part; n ¼ 79 participated and were allocated either to intervention (n ¼ 43) or control (n ¼ 36). The control group received treatment as usual, while the intervention received PATd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It has been reported that music and art therapy combined with CBT improves patients' recognition and acceptance of treatment, reducing depression, anxiety and negative emotional reactions to food, body shape and weight (Wang and Xiao 2021). Another study using manual-based phenomenological art therapy with a 6-month follow-up observed decreased depression and suicidal ideation, improved self-esteem and increased return to work in patients (Blomdahl et al 2022). Our study results show that art therapy promotes faster recovery from depression, an important risk factor in patients with ED, with sustained recovery over time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that music and art therapy combined with CBT improves patients' recognition and acceptance of treatment, reducing depression, anxiety and negative emotional reactions to food, body shape and weight (Wang and Xiao 2021). Another study using manual-based phenomenological art therapy with a 6-month follow-up observed decreased depression and suicidal ideation, improved self-esteem and increased return to work in patients (Blomdahl et al 2022). Our study results show that art therapy promotes faster recovery from depression, an important risk factor in patients with ED, with sustained recovery over time.…”
Section: Discussionmentioning
confidence: 99%
“…The design was a two-armed, small-scale RCT. At the 6-month follow-up time point, a measure of suicidal ideation indicated improvement, as did a measure of self-esteem [ 124 ]. An interesting qualitative study explored the role of dance in “body memory” in people who were bereaved as children/adolescents.…”
Section: Psychological Interventions Which May Support and Help Devel...mentioning
confidence: 99%
“…Systematic reviews have established multiple benefits of art therapy for common mental health conditions, including depression and severe anxiety (7)(8)(9)(10)(11)(12)(13), and demonstrated its success in addressing psychological impacts of long-term or life limiting physical health conditions (14)(15)(16). Evidence is also growing of sustained benefits of art therapy (17,18) and of it being a highly acceptable form of treatment (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%